Joint effects of microplastics and ciprofloxacin on their toxicity and fates in wheat: A hydroponic study. (September 2022) - Ma, Jing; Chen, Fu; Zhu, Yanfeng; Li, Xiaoxiao; Yu, Haochen; Sun, Yan
Abstract: The toxicological impacts of microplastics (MPs) and antibiotics in the soil environment have gradually drawn widespread attention, while little research has focused on the combined pollution of MPs and antibiotics on plants. In this work, a 21-day hydroponic study was conducted to test the hypothesis that polystyrene MPs (0.1, 1 and 10 μm particle sizes, 50 mg/L) and ciprofloxacin (CIP) (1.0 and 5.0 mg/L) had a joint toxicity to wheat seedlings and they could be absorbed by wheat. Plant samples were taken for analyses after 21 days of exposure. The results showed that 0.1 and 1 μm MP could enter wheat roots but only the former could translocate to aerial parts. Moreover, 0.1 μm MP showed a greater toxicity effect than 1 μm MP, whereas 10 μm MP exhibited little toxicity on wheat. The dosing of 0.1 μm MP significantly increased the toxic effects of CIP to wheat. Compared to the control treatment (without MPs and CIP), 0.1 μm MPs-5.0 mg/L CIP treatment resulted in inhibition of root length and weight by 60.1% and 44.3%, respectively, while the contents of chlorophyll a and chlorophyll b decreased by 36.3% and 44.6%, respectively. The presence of CIP (5.0 mg/L) potentially aggravated the combined toxicity. The exposure of 0.1 μm MP significantly reduced root superoxide distumase activity but increased root malondialdehyde content. The amount of CIP in wheat tissues carried by MPs was negligible compared with the uptake quantity of CIP by wheat. Graphical abstract: Image 1 Highlights: IP could aggravate the toxicity of MPs to wheat. MPs played a negligible role in the transfer of CIP in wheat tissues. The toxicity of MPs was closely related to the particle size of MPs.